(3cJGH GNJjGQGJ NGdO GdMcje aj Yde LGHQ Hf MjGf aj GdMceIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdSehGJ hGdCQV Ef GdWHjH GdMGPb GdYGde jfHZi dg Cf jYQa eG jONd ajg aEPG Yde Pdc GHJOGA HeYQaI GdYbGbjQ s
(3BNQgG (B:s
(3aGbHd fUjMI fGUM Pi MceI gPG hPGc HMceI GjbfJg hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs